The Novel Diketopiperazine Derivative, Compound 5-3, Selectively Inhibited the Proliferation of FLT3-ITD Mutant Acute Myeloid Leukemia (AML) Cells - Shijie Bi; Yating Cao; Shiyuan Fang; Yanyan Chu; Zixuan Zhang; Meng Li; Rilei Yu; Jinbo Yang; Yu Tang; Peiju Qiu (Marine Drugs)
The internal tandem duplication mutation of FMS-like tyrosine kinase 3 (FLT3-ITD) is associated with high recurrence and mortality rates in acute myeloid leukemia (AML), making it a critical target for anti-AML therapies. Plinabulin is a diketopiperazines derivative that exhibits extensive anti-cancer potency by targeting β-tubulin. We designed and synthesized a novel FLT3 inhibitor, namely 5-3, based on the structure of plinabulin and evaluated its effect on FLT3-ITD mutant AML cells. The results indicated that 5-3 potently and selectively inhibits the growth of mutant FLT3-expressingleukemia cells, and had no effect on FLT3 wide-type cancer cells, suggesting the antiproliferative activity of 5-3 depends highly on FLT3-ITD expression. Mechanically, 5-3 significantly suppressed the phosphorylation of FLT3 signaling pathway, including STAT5, Erk and Akt. Moreover, the efficiency of compound 5-3 is not associated with Plinabulin’s typical target, β-tubulin. In conclusion, the study identified diketopiperazine derivative as a novel FLT3-ITD selective inhibitor. These results demonstrated that 5-3 might be a drug candidate for the treatment of FLT3-ITD-positive AML.